Attitude towards Zika among frontline physicians in a dengue-endemic country: A preliminary cross-sectional study in Indonesia - Yufika, Amanda; Anwar, Samsul; Maulana, Reza; Wahyuniati, Nur; Ramadana, Rizki R.; Ikram, Ikram; Mudatsir, Mudatsir; Utomo, Prattama S.; Te, Haypheng; Enitan, Seyi Samson; Sirinam, Salin; Müller, Ruth; Setiawan, Abdul Malik (Narra J, 2021)
In dengue-endemic countries such as Indonesia, Zika may be misdiagnosed as dengue, leading to underestimates of Zika disease and less foreknowledge of pregnancy-related complications such as microcephaly. Objective: To assess the attitudes of frontline physicians in a dengue-endemic country toward testing for Zika infection among patients with dengue-like illnesses. Methods: A cross-sectional online survey was conducted among general practitioners (GPs) in Indonesia. The survey assessed their attitude and also collected sociodemographic data, characteristics of their medical education, professional background, and workplace, and exposure to Zika cases. A two-step logistic regression analysis was used to assess possible variables associated with these attitudes. Results: A total of 370 GPs were included in the final analysis of which 70.8% had good attitude. Unadjusted analyses suggested that GPs who were 30 years old or older and those who had medical experience five years or longer had lower odds of having a positive attitude compared to those who aged younger than 30 years and those who had medical experience less than five years, OR: 0.58; 95%CI: 0.37, 0.91 and OR: 0.55; 95%CI: 0.35, 0.86, respectively. No explanatory variable was associated with attitude in the fully adjusted model. Conclusion: Our findings point to younger GPs with a shorter medical experience being more likely to consider testing for Zika infection among their patients presenting with dengue-like illnesses. Strategic initiatives may be needed to enhance older or longer-experienced physicians' capacity in diagnosing Zika infection.